Prefigurative politics between ethical practice and absent promise - Gordon, Uri (Wiley-Blackwell, 2017)
'Prefigurative politics' has become a popular term for social movements' ethos of unity between means and ends, but its conceptual genealogy has escaped attention. This article disentangles two components: an ethical revolutionary practice, chiefly indebted to the anarchist tradition, which fights domination while directly constructing alternatives; and prefiguration as a recursive temporal framing, unknowingly drawn from Christianity, in which a future radiates backwards on its past. Tracing prefiguration from the Church Fathers to politicised re-surfacings in the Diggers and the New Left, I associate it with Koselleck's 'process of reassurance' in a pre-ordained historical path. Contrasted to recursive prefiguration are the generative temporal framings couching defences of means-ends unity in the anarchist tradition. These emphasised the path dependency of revolutionary social transformation and the ethical underpinnings of anti-authoritarian politics. Misplaced recursive terminology, I argue, today conveniently distracts from the generative framing of means-ends unity, as the promise of revolution is replaced by that of environmental and industrial collapse. Instead of prefiguration, I suggest conceiving of means-ends unity in terms of Bloch's 'concrete utopia', and associating it with 'anxious' and 'catastrophic' forms of hope.